2016
DOI: 10.3390/molecules21101367
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study on Anti-Hepatitis C Virus Activity of Spatholobus suberectus Dunn

Abstract: Hepatitis C virus (HCV) infects 200 million people worldwide, and 75% of HCV cases progress into chronic infections, which consequently cause cirrhosis and hepatocellular carcinoma. HCV infection is treated with currently considered standard drugs, including direct anti-viral agents (DAAs), alone or in combination with peginterferon-α plus ribavirin. However, sustained viral responses vary in different cohorts, and high costs limit the broad use of DAAs. In this study, the ethanol and water extracts of 12 herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Determination of total flavonoid content (TFC): The TFC was carried out according to Chen et al. (2016) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of total flavonoid content (TFC): The TFC was carried out according to Chen et al. (2016) .…”
Section: Methodsmentioning
confidence: 99%
“…Determination of total flavonoid content (TFC): The TFC was carried out according to Chen et al (2016). Dry samples (0.3 g) and sonicated in 25 ml of 50% ethanol at a ratio of 1:20 (w/v) for 1 h using a SB-800 DTD sonicator (Ningbo Xinzhi Biotechnology Co., Ltd, Ningbo, China; power: 100 W; frequency: 40 kHz).…”
Section: Total Flavonoid Contentmentioning
confidence: 99%
“…Spatholobus suberectus (SS) Dunn is dried vine widely used in traditional medicine because it possesses pharmacological activities that include improvement of blood circulation, antiplatelet, anti-inflammation, anti-bacterial, neuroprotection, and anti-cancer effects [6,17]. The plant is known to contain many secondary compounds and flavonoids are the major bioactive substances, including 3′,4′,7-trihydroxyglavone, formononetin, calycosin, prunetin, eriodictyol, butin, liquiritigenin, plathymenin, dihydroquercetin and dihydrokaempferol as well as sterols, lignans, anthraquinones and glycosides [7,8,18].…”
Section: Introductionmentioning
confidence: 99%
“…Component analysis of S . suberectus showed that the herb contains various types of phenolic compounds, including flavones, isoflavonoids, flavanones, flavanonols, and chalcones [ 16 ]. The herb has been shown to have diverse benefits including anti-inflammatory, antioxidant, and antirheumatic effects [ 17 ].…”
Section: Introductionmentioning
confidence: 99%